2020
DOI: 10.5993/ajhb.44.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Health Literacy and Decision-making: A Qualitative Study

Abstract: Objective: Adolescents assume increased responsibility for their health, particularly regarding health decision-making for lifestyle behaviors. Prior research suggests a relationship between health literacy (HL) and health behaviors in adolescents. Yet, the specific role of HL in adolescents' health decision-making is unclear. This study qualitatively explored adolescents' use of HL in their health decision-making. Methods: Six focus groups with adolescents (N = 37, Mage = 16.49, 86% girls) were conducted. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…Recent studies suggest that national and local efforts that incorporate key cultural characteristics such as language and context are particularly effective with young people, and potentially effective in reducing high risk sexual behaviors and increasing HIV testing [ 52 , 53 , 54 ]. Additionally, beyond basic health literacy, strengthening individuals interactive health literacy may reduce disparities, promote greater health equity and help to achieve EHE by strengthening individuals’ ability to discuss safer sex negotiation with their peers and sexual partners as well as strengthen their interactions with healthcare providers [ 55 , 56 ]. Finally, to achieve the goals of EHE, in addition to strengthening peer education (i.e., amongst peers and/or sexual partners), greater attentiveness to the dissemination of information regarding sexual health should be integrated into secondary and post-secondary educational contexts as well, as extant studies demonstrate their effectiveness in educational settings [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that national and local efforts that incorporate key cultural characteristics such as language and context are particularly effective with young people, and potentially effective in reducing high risk sexual behaviors and increasing HIV testing [ 52 , 53 , 54 ]. Additionally, beyond basic health literacy, strengthening individuals interactive health literacy may reduce disparities, promote greater health equity and help to achieve EHE by strengthening individuals’ ability to discuss safer sex negotiation with their peers and sexual partners as well as strengthen their interactions with healthcare providers [ 55 , 56 ]. Finally, to achieve the goals of EHE, in addition to strengthening peer education (i.e., amongst peers and/or sexual partners), greater attentiveness to the dissemination of information regarding sexual health should be integrated into secondary and post-secondary educational contexts as well, as extant studies demonstrate their effectiveness in educational settings [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Item separation reliability (0.97) was acceptable. Wright sample-independent reliability statistic was 0.94 with the scores differentiating four levels of performances: Emerging (0-10), Expanding (11)(12)(13)(14)(15)(16)(17)(18)(19), Lower Bridging (20)(21)(22)(23)(24)(25)(26)(27), and Upper Bridging (28)(29)(30). The KR-20 alpha was 0.91.…”
Section: Aahl Compositementioning
confidence: 97%
“…Six focus groups (~8 students/group) were conducted with 9 th -12 th grade high school students (Mean age=16.49, Standard deviation [SD]=1.35, 86.5% girls, 35% non-Hispanic Black, 35% Hispanic/Latinx, 92% free/reduced lunch eligible) to better understand adolescents' de nition and operationalization of HL (full results reported elsewhere (14)). Participants also provided qualitative responses to scenarios related to IHL and CHL.…”
Section: Item Bank Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in their review of the literature, Fleary and colleagues [ 11 ] found that most studies exploring the relationship between adolescents’ HL and health behaviors predominantly assessed FHL. In their qualitative research, Fleary and Joseph [ 14 , 15 ] found that the HL skills adolescents use in their health decision-making encompass Sørenson and colleague’s [ 8 ] HL definition and Nutbeam’s [ 9 ] FHL, IHL, and CHL paradigm. For example, adolescents described being able to ask questions at their doctor’s appointments (IHL) and critically analyze health information provided to them (CHL) as examples of good health decision-making skills.…”
Section: Introductionmentioning
confidence: 99%